Intellectual Property: Need in Technological Society - Riya (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
Property means collection of rights and obligation which shows ownership and gives privilege and liberty to use the property in any manner they want. Property deals with movables, immovable’s, tangible and intangible. With the changing nature of the society, the people enlarge the area of contemplation, and by this they create many types of articles. Copyright and trademark are part of it, they are intellectual property and it comes under the ambit of intangible property. In our modern society, every person who have their creative ideas, artistic works, etc. they want to use it in every way and want to control it and prevents others to use it without their permission and they want to use their intellectual property for their beneficial purpose and control over them. In this type of property, the owner cannot possess their property but have enlarged the area. There are many types of intellectual properties like copyright trademark, patents, geological indications, designs, etc.